I am not just a nurse: the need for a boundaried ethic of care in the context of prolific relationality - Wee Chan Au (Journal of business ethics, 2023)
The Ethics of Care (EoC) theory has been widely applied in the field of management, and there is a growing consensus that it is important to recognise the value and practice of care in the workplace. In this paper, we consider the implications of the EoC at work, and in particular the risks unboundaried care demands may pose to employees who encounter unmanageable "calls to care". We present findings from interviews with 27 nurses in Malaysia, which suggest that the demand to care at work, in addition to demands made in the non-work sphere, may be unmanageable. We argue for a more boundaried approach to the EoC at work with a view to ensuring that in valuing care we do not over-burden the carer.